FLUORESCENCE STUDY ON TRYPTOPHAN–POTASSIUM IODIDE INTERACTION (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
Interaction of tryptophan (Trp) with potassium iodide in aqueous and DMSO containing solutions at 293 and 303 K temperatures has been studied using fluorescence spectroscopy method. It has been shown that Trp fluorescence quenching by KI depends on I– ion mobility, which is affected by the changes in temperature and viscosity of the environment. The physicochemical characteristics of binding process (Kb, n, ΔH, ΔS and ΔG) have been determined in H2O and DMSO containing solutions.
Keywords: tryptophan, potassium iodide, fluorescence quenching, thermodynamic parameters